Can we 'Catch 'em All'? An exploration of the nexus between augmented reality games, urban planning and urban design. Issue 6 (2nd November 2017) - Potts, Ruth; Jacka, Lisa; Yee, Lachlan Hartley
ABSTRACT: Urban planners and designers have spent the last 50 years trying to activate unused public spaces, create walkable cities and encourage sociability through urban design. Pokémon Go has succeeded, almost overnight, to entice people of all demographics into the streets of cities around the world. In fact, many previously underutilized public spaces have suddenly become hot spots for all demographics, playing Pokémon Go and other similar augmented reality games (ARGs). While anecdotally it seems that ARGs activate public spaces, increase community interactions and facilitate exploration of urban spaces, little study has been done on the influence of ARGs on sense of place, or the way in which these games are influencing player engagement with the public spaces they are playing within. This paper reports the findings of a survey of 994 Australian players. The paper explores whether ARGs affect user needs being met in public spaces, and the implications of these findings for urban practitioners.